3.0k views
5 votes
Evaluate the expression 2x + x, when x = -3.

O
A
-12
O B-9
OC -3
ooo

1 Answer

2 votes

Answer:

Option B) -9 is correct

The evaluated given expression when x=-3 is 2x+x=-9

Explanation:

Given expression is 2x+x

Now to evalute the given expression when x=-3 as below :

2x+x when x=-3

That is put x=-3 in the given expression we get

2x+x=2(-3)+(-3)

=-6-3

=-9 ( adding the like terms here )

Therefore 2x+x=-9

The evaluated given expression when x=-3 is 2x+x=-9

Option B) -9 is correct

User Rokhaya
by
5.5k points